Uma estrutura de programação para o desenvolvimento de aplicações de robótica móvel em tempo-real - Rosas, Rodrigo Rosenfeld (2006)
While there are several mobile robots around, it is a common practice to program them using ad hoc solutions. Some projects were created aiming to provide a common interface to support several kinds of mobile robots but none of them seems to have met real world system requirements. Most of them do not care about time restrictions, which are intrinsic to robotic applications. Real-time support is a very important requirement for deterministic behavior. This project compares current robotic frameworks and proposes a new one, based on clear and objective criteria. This framework is designed in top of the Linux operating system, using a real-time extension, for providing a simple, yet flexible, interface, suitable to mobile robotic applications, which have hard real-time requirements. The choice for a real-time extension was Xenomai, although it would be possible to adapt the proposed framework to other extensions, like RTAI or RTLinux. Such framework provides microseconds latency, in addition of easing a lot the development of mobile robotic applications.